Silent Lupus Nephritis: Unmasking the Subtle Burden of Renal Involvement in Systemic Lupus Erythematosus – A Case Report (Community Based Medical Journal, 2023)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease characterized by the involvement of multiple organs, including the kidneys. Lupus nephritis (LN) is a common and severe manifestation of SLE, often leading to renal dysfunction and disease progression. However, some cases of LN can present with minimal or no clinical symptoms, making early detection and intervention challenging. We present a case report of a 26-year-old lady from Bangladesh with "silent" LN, emphasizing the importance of vigilant monitoring and timely diagnosis. The patient initially presented Swelling of lower limbs but did not exhibit overt urinary symptoms or signs of renal dysfunction. Laboratory investigations revealed elevated antinuclear antibodies (ANA), anti-double-stranded DNA (anti-dsDNA) antibodies, and reduced complement levels. Despite the absence of classical clinical features, a renal biopsy was performed due to persistent laboratory abnormalities, which confirmed the presence of LN. The patient's treatment regimen included high-dose corticosteroids and immunosuppressive agents, resulting in clinical improvement and normalization of laboratory parameters. Regular monitoring of renal function and disease activity was crucial in maintaining disease control and preventing further renal damage.CBMJ 2023 July: Vol. 12 No. 02 P: 188-191